The effectiveness of P5 learning in the Merdeka Curriculum on the skills of seventh-grade students at MTs DDI Kulo - Nur Azikin Nur Azikin; Jusman Tang; Firman Firman; Usman M (Universitas Muhammadiyah Enrekang, 2025)
The Pancasila Student Profile Strengthening Project (P5) initiative is one of the important innovations of an independent curriculum designed to develop student competencies holistically, covering aspects of thinking, emotional attitudes, and physical skills. The urgency of this study lies in the need to ensure that the implementation of P5 is able to improve abilities that are relevant to the demands of the modern era. Such as involving the ability to analyze in depth, evaluate information objectively, and make decisions based on logical thinking, collaboration, creativity, and communication, which are very relevant to the demands of the modern world. This study aims to evaluate the extent to which the applied learning can provide effective results. based on P5 on the skills of class VII students at MTs DDI Kulo. This study is expected to contribute to the development of more efficient and useful learning methods, especially in the context of education in madrasas, as well as support the achievement of the goals of the Merdeka Curriculum in forming students with Pancasila characters. The output of this study covers several important aspects. First, this study will produce empirical data on the impact of P5 learning on student skills. Second, the results of this study are expected to provide practical advice for teachers in integrating P5 into the learning process. Third, this study can serve as a basis for educational policies at the madrasah level to strengthen the implementation of the Merdeka Curriculum. With this research, it is expected that students can improve their ability to think critically, work together in teams, and develop creative skills that are applicable. Expressing this text in everyday life means that we not only pay attention to what we know (cognitive aspect), but also how we feel or respond to something (affective aspect), and how we apply that knowledge and feelings in real action (psychomotor aspect) provides insight into how P5 can be implemented effectively in the madrasah environment, especially at MTs DDI Kulo, so as to support the continuous improvement of the quality of education.